The Roles of Openness and Labor Market Institutions for Employment Dynamics during Economic Crises - Gamberoni, Elisa; Uexkull, Erik Von; Weber, Sebastian (World Bank, Washington, DC, 2012)
Employment effects of the recent global economic crisis have differed significantly across countries. An active public debate currently focuses on external shocks and the role of labor market policies as a driver of those differences. In this note, the authors analyze the roles of integration into the global economy and different labor market institutions during different phases of past global economic downturns and domestic banking and debt crises. The authors find that domestic debt and banking crises were much more severe in their impact on employment than were global economic downturns: on average, the reduction in employment growth was more than twice as strong. The authors also find that openness to trade has both deepened the contractionary effects on employment and allowed for a faster recovery. High severance pay dampened the employment effect in both domestic crises and global economic downturns, whereas very high unemployment benefits were associated with stronger reductions in employment growth.